O16-1 ESBL carriage in slaughterhouse workers is associated with occupational exposure. (1st September 2016) - Dohmen, Wietske; Gompel, Liese Van; Schmitt, Heike; Mevius, Dik; Bonten, Marc; Heederik, Dick
Abstract : Introduction: In humans, infections with extended-spectrum beta-lactamase (ESBL) producing Escherichia coli are associated with increased burden of disease and costs. Livestock can carry ESBL, and for farmers ESBL carriage is associated with the presence of ESBL in animals. ESBL carriage in slaughterhouse workers has not been established yet. We investigated the prevalence of ESBL carriage in slaughterhouse workers and its association with occupational exposure. Materials and methods: Human stool samples from 334 employees in a Dutch pig slaughterhouse were obtained. Presence of ESBL was determined by selective plating, PCR, microarray analysis and gene sequencing. Questionnaires were used to collect personal and occupational information, including job function in the slaughter house. Results: The overall prevalence of ESBL carriage was 4.9% (16/334). The most frequent detected ESBL genes were CTX-M-1 (n = 8), CTX-M-15 (n = 3) and CTX-M-27 (n = 2). ESBL carriage was not equally distributed across different job functions in the slaughterhouse. A higher prevalence of ESBL was seen in workers involved in the job tasks 'removal of lungs, heart, liver, tongue' (31%) and 'removal of head and spinal cord' (25%). For further analysis, participants were divided in two groups based on potential exposure in their job title. One group with an assumed higher exposure to ESBL (e.g. stable work, stabbing, dehairing, removal of organs) and another group with an assumed lower exposure to ESBL (e.g. refrigeration, packaging, expedition). In the "higher exposure" group, 10 out of 95 (10.5%) were carrying ESBL versus 6 out of 233 (2.6%) in the "lower exposure" group. Human ESBL carriage was significantly associated with job function in the slaughterhouse (OR = 4.5, CI = 1.6–12.7). Conclusion: Results suggest a higher risk for ESBL carriage in slaughterhouse workers depending on their job title and tasks involved. In combination with environmental exposure data, this information can be used in formal risk assessments.